Study of changes noted in the platelet count in cord blood of neonates born to hypertensive mothers in a tertiary care hospital, Bangalore, India - Gagandeep, Vijayalaxmi; S., Mohinish; K., Mallesh (International Journal of Contemporary Pediatrics, 2020)
Background: Hypertensive disorders of pregnancy pose several problems to both mother and newborn. Complications in new-born like intrauterine death (IUD), intrauterine growth retardation (IUGR), perinatal asphyxia, neonatal sepsis and bleeding disorders are associated with toxemia of pregnancy. To decrease the perinatal morbidity and mortality, babies of hypertensive mothers should be carefully monitored and managed. Aim of this study was to establish the changes in total platelet count in umbilical cord blood. Methods: This is a hospital based prospective observational study which included the babies born to mothers having hypertensive disorders of pregnancy, total cases accounting about 158. Detailed clinical history taken including details of labour and clinical examination done. In all the subjects, 2 ml of umbilical cord blood anticoagulated with EDTA was collected and haematological tests for total platelet count (TPC) count was done. Results: This study shows that the incidence of neonatal thrombocytopenia is 43.67%. The incidence of sepsis among thrombocytopenia group accounts for about 60% in gestational hypertension, 64.2% in pre-eclampsia and 50% in eclampsia group. Conclusions: With respectively, these findings it can be concluded that the incidence of Neonatal Thrombocytopenia is significantly higher in babies born to HDP mothers and it can be taken as a marker to evaluate Sepsis in such a situation in resource limited setting. As less number of studies is available in this area of interest, this study supports the cause.